The enhancement of the dual-layer phosphorus configuration in color uniformity and luminous flux of a light emitting diode - Phuc Dang Huu; Phung Ton That; Phan Xuan Le (Indonesian Journal of Electrical Engineering and Computer Science, 2022)
A solid-state process was used to generate the green phosphor Ca3Si2O4N2:Eu2+. The luminescence characteristics, dispersed reflection spectra, and heat quenching were investigated initially, followed by the white light emitting diodes (wLED’s) manufacture by the Eu2+ stimulated Ca3Si2O4N2 phosphor. Based on the concentration of ion Eu2+, a wide green emission range localized between 510 and 550 nm was seen in Eu2+ -doped Ca3Si2O4N2. In Ca3Si2O4N2, the best doping concentration of Eu2+ was 1 mol%. An electric multipolar interaction process conveys energy among Eu2+ ions, with a necessary conversion distance of around 30.08 Å. Blending a near-ultraviolet (n-UV) light emitting diodes (LED) which has a GaN basis (380 nm) with the blue BaMgAl10O17:Eu2+, the green  Ca3Si2O4N2:Eu2+, and the red Ca3Si2O4N2:Eu2+ phosphors yielded a wLED with a 88.25 color-rendering indice Ra at 6029 K correlating color temperature.  Ca3Si2O4N2:Eu2+ appears to be a promising option to apply as a converting phosphor in wLED applications.